Protein kinase C isozymes regulate matrix metalloproteinase-1 expression and cell invasion in Helicobacter pylori infection - Sokolova, Olga; Vieth, Michael; Naumann, Michael (Gut, 2013)
Background: Protein kinase C (PKC) signalling is often dysregulated in gastric cancer and therefore represents a potential target in cancer therapy. The Gram-negative bacterium Helicobacter pylori, which colonises the human stomach, plays a major role in the development of gastritis, peptic ulcer and gastric adenocarcinoma. Objective: To analyse the role of PKC isozymes as mediators of H pylori-induced pathogenesis. Methods: PKC phosphorylation was evaluated by immunoblotting and immunohistochemistry. Gene reporter assays, RT-PCR and invasion assays were performed to assess the role of PKC in the regulation of activator protein-1 (AP-1), matrix metalloproteinase-1 (MMP-1) and the invasion of H pylori-infected epithelial cells. Results: H pylori induced phosphorylation of PKC isozymes α, Δ, θ in AGS cells, which was accompanied by the phosphorylation of PKC substrates, including PKCμ and myristoylated alanine-rich C kinase substrate (MARCKS), in a CagA-independent manner. Phospholipase C, phosphatidylinositol 3-kinase and Ca2+ were crucial for PKC activation on infection; inhibition of PKC diminished AP-1 induction and, subsequently, MMP-1 expression. Invasion assays confirmed PKC involvement in H pylori-induced MMP-1 secretion. In addition, analysis of biopsies from human gastric mucosa showed increased phosphorylation of PKC in active H pylori gastritis and gastric adenocarcinoma. Conclusion: The targeting of certain PKC isozymes might represent a suitable strategy to interfere with the MMP-1-dependent remodelling of infected tissue and to overcome the invasive behaviour of gastric cancer cells.
CRIS-Team Scopus Importer:2025-03-05